Women’s primary care nursing in situations of gender violence - Visentin, Fernanda; Becker Vieira, Letícia; Trevisan, Ivana; Lorenzini, Elisiane; Franco da Silva, Eveline (Investigación y Educación en Enfermería, 2015)
Objective. Identify the actions conducted by primary health care nurses for women in situations of domestic violence. Methodology. Exploratory-descriptive study with a qualitative approach. Participants were 17 nurses who worked in the Basic Health Unit in a city in the interior of Rio Grande do Sul, Brazil. The data was collected through semi-structured interviews and the information processing was performed using the interview content analysis technique. Results. By acting in a context of the violence, the nurses describe some elements and strategies they use that allow recognition and action to combat violence, namely: acceptance and empathy, establishing a bond of trust between the professional and the woman, dialogue, and intent listening. The limitations mentioned by participants were: lack of professional training to address the situation, feeling of unpreparedness, lack of time for the workload, the professional’s difficulty in recognizing and dealing with violence given its complexity, low efficiency of the service network, and the sense of professional impotence against the gravity and complexity involved in violence. Conclusion. The participants are not adequately prepared to care for women in situations of domestic violence. It is necessary that this issue be addressed in the training of nursing professionals. How to cite this article: Visentin F, Vieira LB, Trevisan I, Lorenzini E, Silva EF. Women’s primary care nursing in situations of gender violence. Invest Educ Enferm. 2015; 33(3):